Performance characterization on downwash flow and spray drift of multirotor unmanned agricultural aircraft system based on CFD - Li, Hongze; Zhu, Hang; Jiang, Zihao; Lan, Yubin (International Journal of Agricultural and Biological Engineering, 2022)
In recent years, multi-rotor Unmanned Aerial Vehicles (UAVs) have been employed in the field of plant protection in China. Spray drift has been considered a major impact in agriculture aerial spraying, and spray quality in the application of plant protection products. The downwash including wake vortices and downward wind field plays a major role in the dispersal and deposition of pesticide spray released by nozzle(s) equipped in aircraft. Differ from the fixed-wing UAV, the downwash flow of multi-rotor UAV resulted from the rotation of the rotor. Therefore, a study on off-target drift and ground deposit concerning the rotor rotation was simulated through a series of Computational Fluid Dynamics (CFD) simulations to obtain the influence of downwash. The discrete Phase Model (DPM) was taken to simulate the motion of droplet particles since it is an appropriate way to simulate discrete phases in the flow field and can track particle trajectory. In this study, the parameters of CFD simulations were acquired by three kinds of actual replicated experiments. The simulation analysis mainly obtains the droplet drift and deposition rule, the influence of eddy current, and downwash flow caused by the rotor rotation. The results showed that the downwash distribution below different rotors was different owing to the flight angle of inclination, “behind” is the greatest, “middle” is secondly, and “forward” is the smallest in value(behind, middle, and forward represent three regions below rotors along flight direction). According to the simulation results, two methods of reducing droplet drift were put forward and specific simulations were carried out to prove their feasibility. The results of this study can provide theoretical support for improving the spray quality of UAVs and reducing the drift of droplets. Keywords: Unmanned Aerial Vehicles, spray drift, downward wind field, rotor rotation, eddy current, downwash distribution DOI: 10.25165/j.ijabe.20221503.7315 Citation: Li H Z, Zhu H, Jiang Z H, Lan Y B. Performance characterization on downwash flow and spray drift of multirotor unmanned agricultural aircraft system based on CFD. Int J Agric & Biol Eng, 2022; 15(3): 1–8.